Dislocation Dynamics in Monocrystalline Si near the Melting Point Studied in Situ by X‐Ray Bragg Diffraction Imaging. Issue 6 (11th March 2022) - Neves Dias, Serge William; Becker, Maike; Ouaddah, Hadjer; Périchaud, Isabelle; Reinhart, Guillaume; Mangelinck-Noël, Nathalie; Regula, Gabrielle
Abstract : To study dislocation dynamics in a model sample, an intrinsic float zone (FZ) Si wafer is chosen as seed to initiate directional solidification. During the temperature ramp, a Von Laue diffraction spot is recorded by a camera. It provides time‐resolved information on the evolution of silicon crystalline quality and on the defect nucleation locations and dynamics. With increasing temperature, dislocations are observed to propagate through the seed starting mainly from the sample edges. The effective thermomechanical local stress is estimated as low as (1.2 ± 0.4) × 10 5  Pa in a thermal gradient of (1.8 ± 0.2) × 10 2  K m −1 . The latter is sufficient to allow dislocation nucleation and motion at temperatures beyond (1523 ± 9) K. Dislocation velocity increases with temperature and reaches a maximum velocity of (3.0 ± 0.5) × 10 −4  m s −1 close to the silicon melting point. From the dislocation velocity measurements as a function of temperature, an activation energy of (3.1 ± 0.6) eV is estimated and this value is discussed, along with dynamical interactions between defects and dislocations. Abstract : Activation energy Q  = (3.1±0.6) eV of dislocation velocity in float zone (FZ) silicon is determined by in situ X‐ray diffraction imaging at 0.33 Hz of the leading segment motion due to the presence of a local thermomechanical‐resolved shear stress as low as (120±40) kPa in the temperature range of 170–30 K below the Si melting temperature ( T m ).